Young children seek out biased information about social groups. Issue 3 (20th June 2017) - Over, Harriet; Eggleston, Adam; Bell, Jenny; Dunham, Yarrow
Abstract: Understanding the origins of prejudice necessitates exploring the ways in which children participate in the construction of biased representations of social groups. We investigate whether young children actively seek out information that supports and extends their initial intergroup biases. In Studies 1 and 2, we show that children choose to hear a story that contains positive information about their own group and negative information about another group rather than a story that contains negative information about their own group and positive information about the other group. In a third study, we show that children choose to present biased information to others, thus demonstrating that the effects of information selection can start to propagate through social networks. In Studies 4 and 5, we further investigate the nature of children's selective information seeking and show that children prefer ingroup‐favouring information to other types of biased information and even to balanced, unbiased information. Together, this work shows that children are not merely passively recipients of social information; they play an active role in the creation and transmission of intergroup attitudes. Abstract : We demonstrate that children seek out information that is biased in favour of their own group. These data suggest that children play an active role in the creation and transmission of intergroup attitudes.